Degradação eletrooxidativa e biológica de corantes em meios aquosos - Aquino, José Mario de (2011)
The electrochemical degradation of the Reactive Red 141, Acid Blue 62 (AB 62), Direct Black 22, and Disperse Orange 29 dyes in a 0.1 M Na2SO4 solution with and without NaCl addition was investigated with Ti-Pt/β-PbO2 and Si/DDB anodes, using a filter-press reactor, and assessed by the experimental design methodology (investigated variables: current density, pH, NaCl concentration, and temperature). Color removal occurred more efficiently in acidic solutions, in the presence of NaCl, whereas COD removal occurred more efficiently in neutral to basic solutions. The addition of NaCl, with the consequent electrogeneration of active chlorine, significantly improved color and COD removal, demanding low charges per unit volume of solution (Qap) treated by indirect oxidation. Hydroxyl or chloro radicals mediated the organic load mineralization, on the anode surface, requiring similar operational conditions for all investigated dyes, with high Qap values. In spite of the higher levels of oxidation and mineralization attained using the Si/DDB anode, the Ti- Pt/β-PbO2 anode could be an interesting option for the decolorization of dyes. Next, the electrooxidation of a real textile effluent was investigated using Nb/DDB and Ti- Pt/β-PbO2 anodes. As a consequence of its high oxidation power, the Nb/DDB anode was more effective in the removal of color and COD than the Ti-Pt/β-PbO2 anode, with higher current efficiencies and low energy consumption (~ 30 kW h m 3). However, detachment and deactivation of the BDD film was observed in some electrolysis conditions. Additionally, the coupling between the biologic method (BM, with swine sludge) and the electrochemical one (EM, using the Ti-Pt/β-PbO2 anode) was investigated for the degradation of dyes, with results depending on the type of dye used. In the BM, the azo dyes only underwent biotransformation, probably yielding aromatic amines. The afterward EM removal of these compounds was difficult; hence, in this case it is better to use EM directly. The AB 62 anthraquinonic dye proved to be highly degradable and, thus, could be degraded using only BM. Prior electrooxidaction of dye solutions followed by coupling with BM resulted in microorganism inhibition, probably due to the electrogenerated oxidants. Finally, the results from the investigation of reaction intermediates for the AB 62 dye suggest that their amount and nature depend on the solution pH as well as on the electrode material used in the electrolysis. On the other hand, the electrogeneration of organochloride compounds is more efficiently avoided in basic solutions.